A method for manufacturing a core-shell hollow structure in which photocatalyst particles self-generate a core

JP2025506077AActive Publication Date: 2025-03-07NECOSH (BEIJING) TECHNOLOGY CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023560491
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-02-22
Publication Date
2025-03-07
Estimated Expiration
2042-02-22

AI Technical Summary

Benefits of technology

【0020】 本開示によって得られる有益な効果は次の通りである。本開示が提供する方法によって、コアシェル中空構造ナノ粒子が得られ、得られたコアシェル中空構造は、触媒反応の活性面を広げ、活性を向上させるとともに、原材料も節約できる。製品の製造過程が相対的に簡単で、条件の制御が容易であり、工業的に大量に生産しやすい。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025506077000001_ABST
    Figure 2025506077000001_ABST
Patent Text Reader

Abstract

A method for producing a core-shell hollow structure in which photocatalytic particles are self-driven to generate cores is disclosed. The method includes the steps of: (1) mixing an alcohol solution of titanium dioxide with tetraoctadecyl orthotitanate to obtain a first solution, the first solution containing modified titanium dioxide nanospheres; (2) injecting air into water by a micro-nano bubble generator, shearing and crushing to obtain a second solution, the second solution containing micro-nano bubbles; (3) mixing the second solution with the first solution under a temperature of 35 degrees Celsius or higher to obtain a third solution; (4) adding ammonia water and tetraethyl orthosilicate solution to the third solution to obtain a fourth solution; and (5) separating, drying the precipitate, and then calcining to obtain core-shell hollow structure nanoparticles. The obtained core-shell hollow structure expands the active surface of the catalytic reaction, improves activity, and is easy to mass-produce industrially due to its simple method.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to the field of polymer materials, and in particular to a method for producing a core-shell hollow structure in which photocatalytic particles are self-driven to generate a core. [Background technology]

[0002] Titanium dioxide is a common semiconductor photocatalytic material. Under the irradiation of light, titanium dioxide can convert light energy into chemical energy and decompose toxic and harmful organic matter within a relatively short time. In addition, titanium dioxide also has the characteristics of high stability, photocorrosion resistance, non-toxicity, etc., and does not cause secondary pollution during the processing process, so it has attracted more and more people's attention in the fields of antibacterial, deodorizing, oil stain decomposition, anti-mold and anti-algae, and air purification. However, catalytic reactions are essentially surface contact reactions, so they only occur on the surface of the material. Therefore, in the case of catalysts, not only is the limited surface area used for catalytic reactions, but it should also bear the task of particle load fixing, which often greatly affects the catalytic effect.

[0003] The core-shell structure is a nanoscale ordered assembly structure formed by one type of nanomaterial wrapping another type of nanomaterial through chemical bonding or other forces. The core-shell structure plays an important role in maintaining the functional stability of the catalyst, adjusting the physicochemical properties of the material to achieve favorable complementarity, preventing the aggregation of nanoparticles, and controlling the particle interface reaction, and has a wide range of application prospects in photocatalysis, batteries, gas storage and separation. However, for nanocatalyst materials that rely on surface area to drive the reaction, how to solve the problem that the core surface is covered with a shell, which causes interference with the catalytic activity of the core, has always been an unavoidable obstacle on the road to the application of nanocatalysts. Summary of the Invention

[0004] The present disclosure aims to solve at least to some extent one of the technical problems of the related art. The present disclosure utilizes the surface interface principle that surface hydrophobic substances have hydrophilic properties, and uses tetraoctadecyl orthotitanate to perform surface hydrophobic modification on commercially available titanium dioxide nanosphere particles. The titanium dioxide particles are then placed in a system of water and micro-nano bubbles, and the difference in surface tension between the hydrophilic and hydrophobic surfaces allows the titanium dioxide particles to self-propel into the micro-nano bubbles. Finally, a silicon dioxide shell is synthesized at the water-air interface of the micro-nano bubbles, resulting in photocatalytic core-shell hollow structure nanoparticles with a hollow structure between the core and shell.

[0005] Specifically, the present disclosure provides the following technical solutions:

[0006] A first aspect of the present disclosure provides a method for producing core-shell hollow structured nanoparticles, the method comprising the steps of: (1) mixing an alcohol solution of titanium dioxide and tetraoctadecyl orthotitanate to obtain a first solution, the first solution containing modified titanium dioxide nanospheres; (2) injecting air into water using a micro-nano bubble generator and shearing and crushing the water to obtain a second solution, the second solution containing micro-nano bubbles; (3) mixing the second solution and the first solution at a temperature of 35 degrees Celsius or higher to obtain a third solution; (4) adding aqueous ammonia and a tetraethyl orthosilicate solution to the third solution to obtain a fourth solution; (5) separating, drying the precipitate, and then calcining to obtain core-shell hollow structure nanoparticles.

[0007] According to the embodiment of the present disclosure, the above-mentioned method for producing core-shell hollow structured nanoparticles may further include the following technical features.

[0008] Furthermore, in step (1), the alcohol solution of titanium dioxide contains 1 to 4 parts by weight of titanium dioxide, and the tetraoctadecyl orthotitanate is 0.1 to 1.5 parts by weight.

[0009] Furthermore, in step (1), the diameter of the titanium dioxide in the alcohol solution of titanium dioxide is 200 to 400 nanometers.

[0010] Furthermore, in step (1), the alcohol solution of titanium dioxide is an ethanol solution of titanium dioxide containing 1 to 4 parts by weight of titanium dioxide and 10 to 50 parts by weight of anhydrous ethanol.

[0011] Furthermore, in step (2), the micro-nano bubbles have a diameter of 600 to 1000 nanometers.

[0012] Furthermore, the shearing and crushing time is 4 to 9 hours.

[0013] Furthermore, in step (2), air is injected into the water by a micro / nano bubble generator. According to a preferred embodiment of the present disclosure, air is injected into the water by the micro / nano bubble generator so that the air humidity is 5% to 30%.

[0014] Furthermore, in step (3), the temperature is 40 degrees Celsius.

[0015] Furthermore, in step (4), the amount of the titanium dioxide in step (1) is calculated as 1 to 4 parts by weight, the amount of the ammonia water is 1 to 10 parts by weight, and the amount of the tetraethyl orthosilicate solution is 2 to 10 parts by weight.

[0016] Furthermore, in step (5), the calcination temperature is 400 to 500 degrees Celsius, and the calcination time is 1 to 3 hours.

[0017] Furthermore, the drying temperature is 70 to 90 degrees Celsius.

[0018] A second aspect of the present disclosure provides a method for producing core-shell hollow structured nanoparticles, the method comprising the steps of: (1) mixing an alcohol solution of titanium dioxide with tetraoctadecyl orthotitanate to obtain a first solution, the first solution containing modified titanium dioxide nanospheres, the alcohol solution of titanium dioxide containing 10-50 parts by weight of anhydrous ethanol and 1-4 parts by weight of titanium dioxide; (2) injecting air into water using a micro-nano bubble generator and shearing and crushing the water to obtain a second solution, the second solution containing micro-nano bubbles, the diameter of the micro-nano bubbles being 600 to 1000 nm; (3) mixing the second solution and the first solution at 40 degrees Celsius to obtain a third solution; (4) adding 1 to 10 parts by weight of aqueous ammonia and 2 to 10 parts by weight of a tetraethyl orthosilicate solution to the third solution to obtain a fourth solution; (5) separating, drying the precipitate, and then calcining to obtain core-shell hollow structure nanoparticles.

[0019] A third aspect of the present disclosure provides core-shell hollow structure nanoparticles produced by the method according to any one of the first or second aspects.

[0020] The beneficial effects of the present disclosure are as follows: the method provided by the present disclosure provides core-shell hollow structure nanoparticles, which can expand the active surface of the catalytic reaction, improve the activity, and save raw materials; the manufacturing process of the product is relatively simple, the conditions are easy to control, and it is easy to mass-produce industrially. [Brief description of the drawings]

[0021] [Figure 1] FIG. 2 is an electron microscope image of a hollow core-shell nanoparticle according to an embodiment of the present disclosure.

[0022] [Diagram 2] FIG. 2 is an EDS energy dispersive spectroscopy diagram of a core-shell hollow nanoparticle according to an embodiment of the present disclosure.

[0023] [Diagram 3] 1 shows XRD data results of the core-shell hollow structure nanoparticles according to an embodiment of the present disclosure.

[0024] [Figure 4] 1 shows the results of a photocatalytic fading experiment of a Rhodamine B solution according to an embodiment of the present disclosure.

[0025] [Diagram 5] 1 shows the results of antibacterial performance tests on Escherichia coli and Staphylococcus aureus according to an embodiment of the present disclosure.

[0026] [Figure 6] FIG. 2 is a diagram showing the results of an electron microscope observation according to Comparative Example 1 of the present disclosure.

[0027] [Figure 7] FIG. 11 is a diagram showing the results of an electron microscope according to Comparative Example 2 of the present disclosure.

[0028] [Figure 8] FIG. 11 is a diagram showing the results of an electron microscope according to Comparative Example 3 of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings. However, the embodiments shown are illustrative for interpreting the present disclosure and should not be understood as limitations on the present disclosure.

[0030] Micro- and nano-bubbles are a special gas state that exists at the interface between gas and liquid, and can exist stably in liquid for a long time, and can be used as a manufacturing template for non-contact catalyst surfaces. Micro- and nano-bubbles can be obtained by commercially available micro- and nano-bubble generators. For example, commercially available micro- and nano-bubbles are high-shear generators, and micro- and nano-bubbles are usually obtained by crushing large gas-liquid mixture bubbles using dynamic or static high-speed shear equipment.

[0031] This disclosure utilizes the surface-interface principle that surface hydrophobic substances have hydrophilic properties, and modifies the surface of hydrophobic titanium dioxide particles, placing them in a system of water and micro-nano bubbles, and allowing the titanium dioxide particles to enter the micro-nano bubbles by self-propulsion due to the difference in the hydrophilic-phobic surface tension. Finally, a silicon dioxide shell is synthesized at the interface between the water and air of the micro-nano bubbles, resulting in photocatalytic core-shell hollow structure nanoparticles with a hollow structure between the core and shell.

[0032] The present disclosure provides a method for producing core-shell hollow structured nanoparticles, the method comprising: (1) mixing an alcohol solution of titanium dioxide and tetraoctadecyl orthotitanate to obtain a first solution, the first solution containing modified titanium dioxide nanospheres; (2) injecting air into water using a micro-nano bubble generator and shearing and crushing the water to obtain a second solution, the second solution containing micro-nano bubbles; (3) mixing the second solution and the first solution at a temperature of 35 degrees Celsius or higher to obtain a third solution; (4) adding aqueous ammonia and a tetraethyl orthosilicate solution to the third solution to obtain a fourth solution; (5) separating, drying the precipitate, and then calcining to obtain core-shell hollow structure nanoparticles.

[0033] There is no particular requirement for the manufacturing order of steps (1) and (2).

[0034] According to a specific embodiment, in step (1), the alcohol solution of titanium dioxide contains 1-4 parts by weight of titanium dioxide, and the tetraoctadecyl orthotitanate is 0.1-1.5 parts by weight. The appropriate content of tetraoctadecyl orthotitanate can play the role of surface hydrophobic modification, so that modified titanium dioxide nanospheres can be obtained.

[0035] According to a specific embodiment, in step (1), the diameter of the titanium dioxide in the alcohol solution of titanium dioxide is 200-400 nanometers.

[0036] According to a specific embodiment, in step (1), the alcohol solution of titanium dioxide is an ethanol solution of titanium dioxide, which comprises 1-4 parts by weight of titanium dioxide and 10-50 parts by weight of anhydrous ethanol.

[0037] According to a specific embodiment, in step (2), the diameter of the micro-nano bubbles is 600-1000 nm, for example, 700-1000 nm, 800-1000 nm, 900-1000 nm, 600-800 nm. The diameter of the micro-nano bubbles directly affects the performance of the core-shell hollow nanoparticles and the size of the space between the core and shell formed to some extent. If the diameter of the micro-nano bubbles is too small, it will affect the loading of the core-shell hollow nanoparticles, and if the diameter of the micro-nano bubbles is too large, the shell layer structure of the core-shell hollow nanoparticles formed will be unstable.

[0038] According to a specific embodiment of the present disclosure, the shear-crushing time is 4 to 9 hours.

[0039] According to a specific embodiment of the present disclosure, in step (2), air is injected into the water by a micro / nano bubble generator.

[0040] According to a specific embodiment of the present disclosure, in step (3), the temperature is 40 degrees Celsius. As the alcohol evaporates, the surface-hydrophobically modified titanium dioxide nanospheres produce hydrophobic and hydrophilic properties due to the action of surface tension, and then self-propel into the interior of the air bubbles (similar to the process of air bubble removal in a water body).

[0041] Tetraethyl orthosilicate can form silicon dioxide under the action of aqueous ammonia. According to a specific embodiment of the present disclosure, in step (4), the amount of the aqueous ammonia is 1-10 parts by weight, and the amount of the tetraethyl orthosilicate solution is 2-10 parts by weight, calculated based on the amount of titanium dioxide in step (1) being 1-4 parts by weight.

[0042] According to a specific embodiment of the present disclosure, in step (5), the calcination temperature is 400-500 degrees Celsius, and the calcination time is 1-3 hours.

[0043] According to a specific embodiment of the present disclosure, the drying temperature is 70 to 90 degrees Celsius.

[0044] The present disclosure will be described in more detail in conjunction with the following examples. The examples are for illustrative purposes only and do not limit the contents of the present disclosure. The following examples are used to interpret the solutions of the present disclosure. Those skilled in the art will understand that the following examples are only for illustrating the present disclosure and should not be considered as limiting the scope of the present disclosure. If no specific techniques or conditions are specified in the examples, they shall be carried out according to the techniques or conditions described in the literature in this field or according to the product specifications. If no manufacturer is specified, the reagents and instruments used are all conventional products that can be purchased on the market.

[0045] Example 1 Example 1 provides a method for preparing core-shell hollow structured nanoparticles, the method includes the following steps:

[0046] 2 parts by weight of commercially available titanium dioxide nanospheres with a diameter of about 200 to 400 nm are added to 1.30 parts by weight of absolute ethanol and stirred uniformly.

[0047] 2. Add 1 part by weight of tetraoctadecyl orthotitanate to the solution obtained in step 1 above and stir for 24 hours to carry out surface hydrophobic modification of the titanium dioxide nanospheres.

[0048] 3. Air is injected into 100 parts by weight of distilled water using a commercially available micro-nano bubble generator, and the gas-liquid is sheared and crushed to obtain micro-nano bubbles. The diameter of the micro-nano bubbles is controlled to around 800 nm, and the shearing time is 6 hours.

[0049] 4. Heat the solution obtained in step 3 to 40 degrees Celsius and then quickly add 10 parts by weight of the solution obtained in step 2.

[0050] Add 5.5 parts by weight of aqueous ammonia to the solution obtained in step 4, and stir vigorously. Then add 5 parts by weight of tetraethyl orthosilicate solution dropwise and stir for 4 hours.

[0051] 6. Finally, the solution obtained in step 5 is centrifuged to obtain the precipitate, which is then dried at 80 degrees Celsius for 12 hours. It is then calcined at 400-500 degrees Celsius for 1-3 hours to obtain the core-shell hollow structure nanoparticles.

[0052] An electron microscope image of the obtained core-shell hollow structure nanoparticles is shown in FIG.

[0053] The produced core-shell hollow nanoparticles were characterized by EDS energy dispersive spectroscopy, and the results are shown in Figure 2. The EDS energy dispersive spectroscopy in Figure 2 shows the ratio of each component element of the core-shell hollow nanoparticles in the photocatalyst.

[0054] In addition, as shown in FIG. 3, the XRD data indicates that the lattice structure of the titanium dioxide particles in the core-shell hollow structure nanoparticles remains unchanged, and the lattice structure parameters are those of standard anatase phase titanium dioxide.

[0055] The photocatalytic bleaching experiment results for Rhodamine B solution are shown in Figure 4. The results show that the core-shell hollow structure nanoparticles can reach 1×10 -5 It has also been shown that it can photocatalytically bleach mol / L of Rhodamine B (RhB) solution, and its catalytic activity is higher than that of untreated titanium dioxide particles under the same conditions.

[0056] The antibacterial test results for E. coli and Staphylococcus aureus are shown in Figure 5. The results also show that the samples with added core-shell hollow titanium nanoparticles (numbers 5 and 6 in Figure 5b) exhibit the highest antibacterial performance compared to the blank samples without added titanium dioxide (numbers 1 and 2 in Figure 5b) and the samples with added titanium dioxide (numbers 3 and 4 in Figure 5b).

[0057] Example 2 Example 2 provides a method for preparing core-shell hollow structured nanoparticles, the method includes the following steps:

[0058] Add 4 parts by weight of commercially available titanium dioxide nanospheres with a diameter of about 200 to 400 nm to 1.50 parts by weight of absolute ethanol and stir uniformly.

[0059] 2. 1.5 parts by weight of tetraoctadecyl orthotitanate is added to the above obtained solution and stirred for 40 hours to carry out surface hydrophobic modification of the titanium dioxide nanospheres.

[0060] 3. Air is injected into 100 parts by weight of distilled water using a commercially available micro-nano bubble generator, and the gas-liquid is sheared and crushed to obtain micro-nano bubbles. The diameter of the micro-nano bubbles is controlled to around 1000 nm, and the shearing time is 8 hours.

[0061] 4. Heat the solution obtained in step 3 to 40 degrees Celsius, then quickly add 20 parts by weight of the solution obtained in step 2.

[0062] 5. Add 10 parts by weight of aqueous ammonia to the solution described in step 4 and stir vigorously, then add 10 parts by weight of tetraethyl orthosilicate solution dropwise and stir for 4 hours.

[0063] 6. Finally, the solution obtained in step 5 is centrifuged to obtain the precipitate, which is then dried at 80 degrees Celsius for 12 hours. It is then calcined at 400-500 degrees Celsius for 1-3 hours to obtain the core-shell hollow structure nanoparticles.

[0064] The core-shell hollow structure nanoparticles produced in Example 2 were subjected to the same characteristic evaluation as in Example 1, and the results showed that they exhibited the same characteristics as the core-shell hollow structure nanoparticles produced in Example 1.

[0065] Comparative Example 1 During the experiment, it was found that if tetraoctadecyl orthotitanate is not used during the hydrophobic modification of the surface of titanium dioxide nanospheres, the surface will not be sufficiently hydrophobic, and the surface tension provided by the present disclosure will not be able to produce hydrophobic and hydrophilic properties, and the process of self-propelled entry into the interior of the bubbles will not be formed, as shown in Figure 6. Similarly, if the amount of tetraoctadecyl orthotitanate is insufficient, it will also affect the structure and performance of the core-shell hollow structure nanoparticles formed.

[0066] Comparative Example 2 During the research, it was found that in the process of tetraethyl orthosilicate synthesizing silicon dioxide shell at the water-air interface through the action of ammonia water, the formation of silicon dioxide reaction is too fast, so the shell structure cannot be formed, as shown in Figure 7. Therefore, when adding tetraethyl orthosilicate solution, it should be added dropwise.

[0067] Comparative Example 3 During the research, it was discovered that in the process of tetraethyl orthosilicate synthesizing a silicon dioxide shell at the water-air interface through the action of ammonia water, as shown in Figure 8, adding too much tetraethyl orthosilicate solution will result in an excess of silicon dioxide in the system, causing the self-aggregation phenomenon of silicon dioxide and affecting the formation of a normal shell structure.

[0068] It should be noted that the above description is only a preferred embodiment of the present disclosure, and a person skilled in the art may further make some improvements and modifications without departing from the principle of the present disclosure, and these improvements and modifications should also be regarded as the protection scope of the present disclosure.

Claims

1. A method for producing core-shell hollow structure nanoparticles, comprising the steps of: (1) mixing an alcohol solution of titanium dioxide and tetraoctadecyl orthotitanate to obtain a first solution, the first solution containing modified titanium dioxide nanospheres; (2) A step of injecting air into water using a micro-nano bubble generator and shearing and crushing the water to obtain a second solution, the second solution containing micro-nano bubbles; (3) mixing the second solution and the first solution at a temperature of 35 degrees Celsius or higher to obtain a third solution; (4) adding ammonia water and tetraethyl orthosilicate solution to the third solution to obtain a fourth solution; (5) Separating, drying the precipitate, and then calcining to obtain core-shell hollow structure nanoparticles. The method according to claim 1, further comprising:

2. In step (1), the alcohol solution of titanium dioxide contains 1 to 4 parts by weight of titanium dioxide, and the tetraoctadecyl orthotitanate is 0.1 to 1.5 parts by weight; Optionally, the method of claim 1, wherein in step (1), the diameter of the titanium dioxide in the alcohol solution of titanium dioxide is 200 to 400 nanometers.

3. 2. The method according to claim 1, wherein in step (1), the alcohol solution of titanium dioxide is an ethanol solution of titanium dioxide comprising 1-4 parts by weight of titanium dioxide and 10-50 parts by weight of anhydrous ethanol.

4. In step (2), the diameter of the micro-nano bubbles is 600 to 1000 nanometers; Optionally, the shear-grinding time is between 4 and 9 hours.

5. The method according to claim 1, wherein in step (2), air is injected into the water by a micro-nano bubble generator so that the air humidity is 5% to 30%.

6. 2. The method of claim 1, wherein in step (3), the temperature is between 40 and 50 degrees Celsius.

7. The method according to claim 1, wherein in step (4), the amount of the ammonia water is 1-10 parts by weight, and the amount of the tetraethyl orthosilicate solution is 2-10 parts by weight, calculated as 1-4 parts by weight of the titanium dioxide in step (1).

8. In step (5), the calcination temperature is 400-500 degrees Celsius, and the calcination time is 1-3 hours; Optionally, the drying temperature is between 70 and 90 degrees Celsius.

9. A method for producing core-shell hollow structure nanoparticles, comprising the steps of: (1) mixing an alcohol solution of titanium dioxide with tetraoctadecyl orthotitanate to obtain a first solution, the first solution containing modified titanium dioxide nanospheres, the alcohol solution of titanium dioxide containing 10-50 parts by weight of absolute ethanol and 1-4 parts by weight of titanium dioxide; (2) A step of injecting air into water using a micro-nano bubble generator and shearing and crushing the water to obtain a second solution, the second solution containing micro-nano bubbles, the diameter of the micro-nano bubbles being 600 to 1000 nm; (3) mixing the second solution and the first solution at 40 degrees Celsius to obtain a third solution; (4) adding 1 to 10 parts by weight of ammonia water and 2 to 10 parts by weight of tetraethyl orthosilicate solution to the third solution to obtain a fourth solution; (5) Separating, drying the precipitate, and then calcining to obtain core-shell hollow structure nanoparticles. The method according to claim 1, further comprising:

10. 10. Core-shell hollow structure nanoparticles produced by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing interface optical catalyst

    CN101099929A

  • Efficient sterilization photocatalyst material used for indoor air purification, and preparation method thereof

    CN109221251A

  • SiO2@TiO2 nano composite material as well as preparation method and application thereof

    CN112915989A

  • Method for producing hollow particle

    JP2007075660A

  • Photocatalyst included in hollow porous shell layer and its manufacturing method

    JP2008284411A